2018
DOI: 10.1016/j.fertnstert.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antithyroid antibodies and euploid miscarriage in women with recurrent early pregnancy loss

Abstract: Our study did not demonstrate an association between euploid miscarriage and maternal antithyroid antibodies in subjects with a history of REPL. Therefore, testing or treatment in this cohort may not be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Iravani 17 excluded some participants who had serum TSH levels outside the reference range. In the other studies (Mecacci 2000, 47 Lata 2013, 41 Curve 49 ), the TSH level was significantly higher than normal (>2.5 mIU/L). The data from Curve 49 included some subclinical hypothyroidism patients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Iravani 17 excluded some participants who had serum TSH levels outside the reference range. In the other studies (Mecacci 2000, 47 Lata 2013, 41 Curve 49 ), the TSH level was significantly higher than normal (>2.5 mIU/L). The data from Curve 49 included some subclinical hypothyroidism patients.…”
Section: Discussionmentioning
confidence: 68%
“…We examined the difference of mean basal serum TSH between the TPO‐Ab‐positive and TPO‐Ab‐negative group. Six studies compared it with and without TPO‐Ab 2,17,41,47‐49 . From the meta‐analysis, it emerged that TPO‐Ab‐positive women had significantly higher serum TSH levels (random‐effect SMD = 0.60; 95% CI, 0.31 to 0.90; P < .0001; Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The 2017 ATA guidelines conclude that, "the data for an association between thyroid antibodies and recurrent pregnancy loss are less robust than for sporadic loss." The study by Cueva et al (37) supports this statement. However, the presence or absence of an association remains an open question, and additional studies will be required to fully answer this question.…”
Section: B) Autoimmunity and Recurrent Miscarriage (Question 17)mentioning
confidence: 78%
“…One study was published on thyroid autoimmunity in recurrent pregnancy loss. In an observational study of 74 American women with recurrent early pregnancy loss, Cueva et al found no difference in the frequency of euploid miscarriage in women with or without thyroid autoimmunity, 42% (5/12) vs. 56% (28/50), respectively, P > 0.05 (37). The 2017 ATA guidelines conclude that, "the data for an association between thyroid antibodies and recurrent pregnancy loss are less robust than for sporadic loss."…”
Section: B) Autoimmunity and Recurrent Miscarriage (Question 17)mentioning
confidence: 99%
“…The role of thyroid autoantibodies in recurrent pregnancy loss has also been studied. A small observational cohort study of pregnant people in the United States with a history of recurrent pregnancy loss found no difference in miscarriage frequency between persons who are positive for thyroid autoantibodies (either euthyroid or with subclinical hypothyroidism) and those without these autoantibodies 33 . In contrast, the 2020 systematic review by Dong et al reported a significant association between thyroid autoimmunity and recurrent pregnancy loss (OR, 1.94; 95% CI, 1.43‐2.64; no P value included) 32 .…”
Section: Pathophysiology Of Hypothyroidism In Pregnancymentioning
confidence: 99%